Detailed spatiotemporal brain mapping of chromatic vision combining high‐resolution VEP with fMRI and retinotopy. Issue 7 (13th March 2018) - Pitzalis, Sabrina; Strappini, Francesca; Bultrini, Alessandro; Di Russo, Francesco
Abstract: Neuroimaging studies have identified so far, several color‐sensitive visual areas in the human brain, and the temporal dynamics of these activities have been separately investigated using the visual‐evoked potentials (VEPs). In the present study, we combined electrophysiological and neuroimaging methods to determine a detailed spatiotemporal profile of chromatic VEP and to localize its neural generators. The accuracy of the present co‐registration study was obtained by combining standard fMRI data with retinotopic and motion mapping data at the individual level. We found a sequence of occipito activities more complex than that typically reported for chromatic VEPs, including feed‐forward and reentrant feedback. Results showed that chromatic human perception arises by the combined activity of at the least five parieto‐occipital areas including V1, LOC, V8/VO, and the motion‐sensitive dorsal region MT+. However, the contribution of V1 and V8/VO seems dominant because the re‐entrant activity in these areas was present more than once (twice in V8/VO and thrice in V1). This feedforward and feedback chromatic processing appears delayed compared with the luminance processing. Associating VEPs and neuroimaging measures, we showed for the first time a complex spatiotemporal pattern of activity, confirming that chromatic stimuli produce intricate interactions of many different brain dorsal and ventral areas.